Randomized Trial of Irinotecan and Cetuximab With or Without Vemurafenib in BRAF-Mutant Metastatic Colorectal Cancer (SWOG S1406). Issue 4 (1st February 2021) - Kopetz, Scott; Guthrie, Katherine A.; Morris, Van K.; Lenz, Heinz-Josef; Magliocco, Anthony M.; Maru, Dipen; Yan, Yibing; Lanman, Richard; Manyam, Ganiraju; Hong, David S.; Sorokin, Alexey; Atreya, Chloe E.; et al.
Abstract : PURPOSE: BRAF V600E mutations are rarely associated with objective responses to the BRAF inhibitor vemurafenib in patients with metastatic colorectal cancer (CRC). Blockade of BRAF V600E by vemurafenib causes feedback upregulation of EGFR, whose signaling activities can be impeded by cetuximab. METHODS: One hundred six patients with BRAF V600E -mutated metastatic CRC previously treated with one or two regimens were randomly assigned to irinotecan and cetuximab with or without vemurafenib (960 mg PO twice daily). RESULTS: Progression-free survival, the primary end point, was improved with the addition of vemurafenib (hazard ratio, 0.50, P = .001). The response rate was 17% versus 4% ( P = .05), with a disease control rate of 65% versus 21% ( P < .001). A decline in circulating tumor DNA BRAF V600E variant allele frequency was seen in 87% versus 0% of patients ( P < .001), with a low incidence of acquired RAS alterations at the time of progression. RNA profiling suggested that treatment benefit did not depend on previously established BRAF subgroups or the consensus molecular subtype. CONCLUSION: Simultaneous inhibition of EGFR and BRAF combined with irinotecan is effective in BRAF V600E -mutated CRC.